The The nexus of management model and social transformation: A case study of da'wah strategy at the Jogokariyan mosque - Arsam, Arsam; Majid, Nik Suhaida Nik Abdul; Amaludin, Asep (Jurnal Ilmu Dakwah, 2025)
Purpose – This study aims to analyze the da'wah strategy implemented by the Jogokariyan Mosque management in driving social transformation within the community of Mantrijeron, Yogyakarta. Method – Using a qualitative approach with a case study design, the research explores the Mosque's da'wah strategy in depth through interviews, participatory observation, and documentation studies. Result  –  These findings reveal that the success of the Mosque lies in synergizing modern management with da’wah through a comprehensive strategy that integrates three main approaches: sentimental, rational, and sensory-based. This approach is built upon three core pillars: transparent financial management using a ‘zero-balance’ principle, community economic empowerment through business capital programs and food assistance, and the restoration of the Mosque’s function as a diverse community activity center. Implication – The study implies that Mosques can serve as effective and sustainable catalysts for socioeconomic development. The research result demonstrates that religious institutions can be relevant and solution-oriented agents of change in the modern era. Originality/Value – This research addresses a gap in the existing literature regarding the Mosque's role as an agent of holistic change, especially given the persistent structural challenges, such as poverty and destructive social behaviors, prevalent in the area. Its originality lies in the integrated. *** Tujuan - Penelitian ini bertujuan untuk menganalisis strategi dakwah yang diterapkan oleh pengurus Masjid Jogokariyan dalam mendorong transformasi sosial di lingkungan masyarakat Mantrijeron, Yogyakarta. Metode - Menggunakan pendekatan kualitatif dengan desain studi kasus, penelitian ini mengeksplorasi strategi dakwah Masjid secara mendalam melalui wawancara, observasi partisipatif, dan studi dokumentasi. Hasil - Temuan ini mengungkapkan bahwa keberhasilan Masjid adalah mensinergikan antara manajemen modern dan dakwah dan strategi dakwah komprehensif yang mengintegrasikan tiga pendekatan utama: sentimental, rasional, dan berbasis sensorik. Pendekatan ini dibangun di atas tiga pilar inti: pengelolaan keuangan yang transparan dengan prinsip 'zero-balance', pemberdayaan ekonomi masyarakat melalui program modal usaha dan bantuan pangan, serta restorasi fungsi Masjid sebagai pusat kegiatan masyarakat yang beragam Implikasi - Studi ini menyiratkan bahwa Masjid dapat berfungsi sebagai katalis yang efektif dan berkelanjutan untuk pembangunan sosial-ekonomi. Hasil penelitian menunjukkan bahwa lembaga keagamaan dapat menjadi agen perubahan yang relevan dan berorientasi pada solusi di era modern. Orisinalitas/Nilai - Penelitian ini membahas kesenjangan dalam literatur yang ada mengenai peran Masjid sebagai agen perubahan holistik, terutama mengingat tantangan struktural yang terus-menerus seperti kemiskinan dan perilaku sosial yang merusak yang lazim di daerah tersebut. Orisinalitasnya terletak pada yang terintegrasi.